Culture As A Catalyst: : Unveiling The Nexus Between Health Services Performance Management and National Identity - Komalasari, Rita (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2023)
The study aims to examine the effects of performance management in health care via the prism of national culture. The study presents a review synthesis of a research report on performance evaluation. The research method used is narrative review. In today's corporate environment, when firms are increasingly competing worldwide, this is a must. As a result, workers and company executives alike must grapple with how easily rules and procedures created in one country may apply to other nations' operations. Some have argued for worldwide standardization in this field to save money and take advantage of economies of scale. Researchers in international business and cultural studies have suggested that cultural differences influence every company's activity. In contrast, some others have urged adopting organizational procedures when enterprises move across international borders. This article presents a meta-ethnographic synthesis of research on professional contacts with performance evaluation. Forty-four papers were analyzed. The results study show that performance management organizations affect the results of evaluations and give some good ideas for more research. The implication of the result is that performance management organizations have an impact on the outcomes of evaluations. Keywords: business, health-related, organizational processes, performance management. JEL: A11, A13